Standards-based physical education curriculum development - Lund, Jacalyn Lea 1950-; Tannehill, Deborah
This innovative guide teaches students about the process of writing curriculum in physical education and was written by experts who have had specific experience designing and implementing this thematic curriculum. The text begins by looking at the national physical education standards and then examines physical education from a conceptual standpoint, addressing the "so what" of physical education. It then goes on to examine the development of performance-based assessments designed to measure the extent of student learning